COVID-19 and its prevention in internally displaced person (IDP) camps in Somalia: impact on livelihood, food security and mental health - Farah I. Mumin; Fred D. Wesonga; Jibril I. M. Handuleh; Ross G. White; Siobhan M. Mor (BMC, 2022)
Abstract Background Somalia has over 2.6 million internally displaced people (IDP) that depend on daily wages and humanitarian assistance for their livelihoods. This study investigated the impact of COVID-19 on livelihoods, food security and mental health of Somalia's IDPs. Methods A questionnaire was conducted with "breadwinners" (n = 585) residing in 15 randomly selected IDP camps. Mental health was assessed using the 5-item World Health Organization Wellbeing Index (WHO-5) and the Patient Health Questionnaire-9 (PHQ-9). Multivariable regression was used to explore the effect of depressive symptoms on soap use and ability to pay for food/medicine/rent. Results Knowledge of COVID-19 symptoms, transmission and prevention was relatively high, however only 55% reported using soap for hand washing. Around one third perceived that prohibition of public gatherings had negatively impacted weekly earnings. Participants reported difficulty buying food (85%), medicine (82%) and paying rent (51%) because of COVID-19. The majority were assessed as having low wellbeing and high depressive symptoms (mean WHO-5 = 44.2/100; mean PHQ-9 = 18.6/27), with most (74%) indicating that they felt worse than before the pandemic. Compared to people with low depressive symptoms, people with high depressive symptoms were less likely to use soap (aOR = 0.3, 95% CI = 0.2, 0.7; P < 0.001) and more likely to report difficulty buying food (aOR = 2.2; 95% CI = 1.1, 4.3; P = 0.02). Conclusion COVID-19 and associated restrictions have negatively impacted Somalia's internally displaced population. Livelihood and mental health support is urgently needed in the recovery phase of the pandemic and should be factored into future pandemic planning.